Advanced ceramic grinding process combined to hazard mitigation to the employees’ health by using an alternative lubri-refrigeration technique - Fernandes, Lucas de Martini [UNESP]; Javaroni, Rafael Liberatti [UNESP]; Rodrigues, Matheus de Souza [UNESP]; Ávila, Benício Nacif [UNESP]; Moraes, Douglas Lyra de [UNESP]; Ribeiro, Fernando Sabino Fonteque; Rodrigues, Alessandro Roger; França, Thiago Valle [UNESP]; Sanchez, Luiz Eduardo de Angelo [UNESP]; Bianchi, Eduardo Carlos [UNESP]; Lopes, José Claudio [UNESP] (Springer Nature, 2023)
The sustainable industry is becoming a global trend that aims to align productivity, quality, and environmental preservation. In the grinding process, the need arises to develop new technologies to replace cutting fluids, which are highly toxic substances. The minimum quantity of lubrication (MQL) technique is alternative lubrication and cooling method that makes machining more ecological. However, its application is still tiny due to its low cooling power and cleaning of the workpiece-tool interface. On the other hand, the grinding conditions improve when associated with the wheel cleaning jet (WCJ) system, which consists of applying an inclined compressed air jet on the grinding wheel, avoiding clogging and the adhesion of chips on the surface of the grinding wheel. From this perspective, this work aims to perform a comparative analysis between the flood method and the MQL and MQL + WCJ techniques, in the external cylindrical grinding of alumina ceramic (Al2O3), at feed rates of 0.25, 0.50, and 0.75 mm/min. The output parameters analyzed will be diametrical wheel wear, G-ratio, surface roughness, roundness error, grinding power, cost, and pollution analysis. The G-ratio was 40% better using MQL + WCJ compared to MQL, while the grinding cost per piece with MQL + WCJ represented about 24% of the price of the conventional method. The results show that the association of WCJ to MQL improves the efficiency of the MQL technique, guaranteeing good results and being an eco-friendly technique.
Keywords: Alumina; Cutting fluid; Environment; Grinding; Minimum quantity lubrication (MQL)